The effect of temperature on polymethyl methacrylate acrylic (PMMA) - Muhammad Farhan, Adnan (2013)
This research is about the effect of temperature onpolymethyl methacrylate. From the investigation of thermo-mëchanical properties of polymethyl methacrylate or PMIVIA, the film of PMMA has been prepared. The glass transition temperature of pure PMMA sample has also been obtained in order to determine its physical state and its influence in other properties such as toughness and stiffness. An effort has also been made to study the storage modulus (E'), loss modulus (E") and Tan 6 in a temperature range from 32°C to 140°C by DMA. It has been observed that storage modulus decreases with temperature due to thermal expansion of films. On the other hand Tan 6 increases up to glass transition temperature beyond which it shows decreasing trend towards melting. Glass transition temperature (Tg) is found to be 82.1°C. The stress strain curves of PMMA films at room temperature and at different temperature (32 0 C-90°C) have been obtained. The results show that the mechanical properties i.e. Young modulus, toughness and tensile strength decrease with increasing temperature whereas the elongation at break shows increasing behavior with temperature in Table 1: PMMA on the effect of temperature. This trend in the different mechanical properties is explained on the basis of free volume theory. The references are from F.S Robert (2012). Thermal Analysis of Materials.Materials Engineering.Marcel Dekker, Inc. p. 2. ISBN 0-8247- 8963-6, U.F Hans (2010). The Dynamics of Heat (2ed.).Springer.p. 211. ISBN 978-14419-7603-1, Kutz, Myer (2002). Handbook of Materials Selection.John Wiley & Sons.p. 341. ISBN 0-471-35924-6.